A chemophenetic study of the genus Maytenus s.l. (Celastraceae): contribution to the rational search of its bioactive metabolites - Lorena Diniz Guimarães; Fernanda Moreira do Amaral; Natalia Barros dos Santos; Ana Joffily; Maria Carolina Anholeti; Selma Ribeiro de Paiva (Rodriguésia, 2020)
Abstract Maytenus s.l. is a genus of the Celastraceae family and many of its species are used in traditional medicine. Most of the substances responsible for the biological activities of plants come from their secondary metabolism, such as terpenoids and flavonoids, which have multiple functions in the plant and can occur in a similar way in plant groups. Chemophenetics analyzes the occurrence of these substances in a taxon and can infer evolutionary trends and contribute to the rational search for new drugs. Chemosystematic parameters were used to analyze the data obtained through a bibliographic survey. The species of Maytenus s.l. were separated into three groups: species with accepted names, synonymous species with the genus Monteverdia and synonymous species with the genus Gymnosporia. Due to their great occurrence and structural variety in Maytenus s.l., triterpenes were chosen as chemosystematic markers, with friedelanes and quinone methide triterpenes being the most expressive types. Studies have already demonstrated the analgesic potential of quinone methides and the antitumor potential of phenolic triterpenes and dimers of these units. Together, the three classes assist in the circumscription of Maytenus s.s. and Monteverdia, while lupanes can be used in the separation of these genera. Oleanans are representative of Gymnosporia.